Biotecnología: trigo para celíacos y arroz enriquecido con lisina - Méndez, Laura (2016)
The major importance of transgenic products at the commercial level is between soybeans, maize, cotton and canola. The objective of modifying crops is not only due to agronomic characteristics, taste and appearance but also the interest to improve the nutritional content of crops and eliminate genes that cause allergies for certain people. The present article describes the reason why studies were carried out to eradicate the gene encoding gliadins in wheat, proteins associated with gluten content. If the goal is achieved many celiacs around the world could consume more wheat products at a lower cost than the current one. There is a large number of the population that can not include in their diets products made from wheat that for the vast majority of people are part of the daily diet because of their energy, protein, minerals and vitamins.